POLITIK HUKUM TERHADAP KOPERASI INDONESIA - Agus Bambang Nugraha (Cakrawala Jurnal Penelitian Sosial, 2016)
Cooperatives are economic institutions whose existence is mandated by the 1945Constitution of Article 33 paragraph (1) of the 1945 Constitution states that: "Theeconomy is structured as a joint venture based on the principle of the family." Theposition of the cooperative as a pillar of the economy, has a position parallel to and onpar with the other pillars, namely the economy under State sector and the private sectoreconomy.In such conditions, this research to be interesting, especially to uncover the political shiftin the law as a result of the application of Law No. 17 in 2012 replacing Law No. 25, 1992.The problems of the application of Law No. 17 in 2012 to more crucial since theConstitutional Court (MK) granted the petition for judicial review of Law No. 17 in 2012through the Decision on Case No. 28 / PUU-X / 2013. Constitutional Court's decisionwhich is erga omnes further confirmed that Law No. 17 in 2012 is diametrically opposedto the values (values) are contained in the 1945 Constitution.The results of the analysis of that Law No. 17 of 2012 has come out or contrary to thephilosophy of the cooperative which is a joint venture based on family principles. Inaddition, Act No. 17 of 2012 concerning Cooperatives in juridical and sociological side hasbeen opposed to the capitalist system, the state is supposed to protect the small people'seconomy, the cooperatives. Such protection are to maintain the philosophy, values, andprinciples of cooperatives of other ideologies among other threats capitalism andcommunism. Thus the cancellation of Law No. 17 in 2012 with the re-enactment of LawNo. 25, 1992, this has resulted that the Cooperative is not lost 'spirit' as a driver ofdevelopment and development of cooperation.Keywords: Cooperative, Law, Political Shift, System of Capitalism